JOHN AKOMFRAH E ISAAC JULIEN: MIGRANDO ENTRE IDEAS, FORMAS Y PLATAFORMAS DE EXHIBICIÓN - Beatriz LEAL RIESCO (Fonseca, Journal of Communication, 2023)
The Afro-diasporic artistsan Isaac Julien (Londres, 1960) and John Akomfrah (Ghana,1957) have overtaken international museums and galleries in recent years. Their writings, their public presentations, and their extensive careers, with works that travel across numerous spaces (cinema, television screen, white cube) have reached a unique position among those of the black diaspora, have allowed them to devote themselves freely to multi-screen works